Motion characteristics and plasma integrity evaluation of Murrah buffalo semen (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Buffalo semen collected from Murrah bull were cryopreserved and evaluated for different motility parameter, kinematics and plasma membrane integrity. Buffalo bulls were maintained uniform standard management and nutritional practices. Semen was collected regularly twice a week semen collection schedule from four (04) Murrah bull. Collected semen was immediately transported to laboratory and evaluated for different macroscopic parameter (color, volume and thickness). Fresh semen was then diluted with saline solution and evaluated for sperm concentration, motility, sperm kinematics and morphology. Semen samples that fill all the standard were selected for freezing and diluted with Tris-egg yolk citrate diluter. Diluted semen was equilibrated, cryopreserved and finally evaluated for post thaw sperm quality. Different motility parameter (total, progressive, static and slow motility) varied significantly (p